The association between anemia and falls in community-living women and men aged 65 years and older from the fifth Tromsø Study 2001-02: a replication study - Hopstock, Laila Arnesdatter; Utne, Elisabeth Bøe; Horsch, Alexander; Skjelbakken, Tove (BMC Geriatrics, 2017)
Source at: https://doi.org/10.1186/s12877-017-0689-8 Background: Falls are common among elderly people, and the risk increase with age. Falls are associated with both health and social consequences for the patient, and major societal costs. Identification of risk factors should be investigated to prevent falls. Previous studies have shown anemia to be associated with increased risk of falling, but the results are inconsistent. The aim of this study was to investigate the association between anemia and self-reported falls among community-living elderly people. The study is a replication of the study by Thaler-Kall and colleagues from 2014, who studied the association between anemia and self-reported falls among 967 women and men 65 years and older in the KORA-Age study from 2009. Methods: We included 2441 participants (54% women) 65 years and older from the population-based Tromsø 5 Study 2001-2002. Logistic regression models were used to investigate the association between anemia (hemoglobin <12 g/ dL in women and <13 g/dL in men) or hemoglobin level and self-reported falls last year, adjusted for sex, age, medication use and disability. Further, associations between combinations of anemia and frailty or disability, and falls, were investigated. Results: No statistical significant associations were found between anemia and falls (OR 95% CI: 0.83, 0.50-1.37) or hemoglobin level and falls (OR, 95% CI: 0.94, 0.81-1.09), or with combinations of anemia and frailty or disability, and falls (OR, 95%: CI: 0.94, 0.40-2.22 and 0.78, 0.34-1.81, respectively). Conclusions: In this replication analysis, in accordance with the results from the original study, no statistically significant association between anemia or hemoglobin and falls was found among community-living women and men aged 65 years or older.